Growth and Passive Q-Switching Application of Cr:TiTe3O8 Crystal - Chengcheng Li; Zeliang Gao; Zhongjun Zhai; Shuai Ye; Youxuan Sun (Crystals, 2022)
A Cr4+-doped TiTe3O8 crystal with dimensions up to 21 mm × 21 mm × 11 mm was grown successfully by the top-seeded solution growth method. A high-resolution X-ray diffraction experiment showed that the full width at half-maximum of the rocking curve was 41.90″. Energy-dispersive spectrometry (EDS) and X-ray fluorescence spectroscopy (XRF) proved that Cr4+ ions have been doped into the TiTe3O8 crystal with molar percentage of 4.9%. The Cr:TiTe3O8 crystal exhibited an absorption range from 995 to 1565 nm, which is suitable for passive Q switch at 1064 nm. Then, a passive Q-switching solid-state laser operating at 1064 nm was realized using a Cr:TiTe3O8 crystal as the saturable absorber. The maximum laser pulse energy is calculated to be 0.7 μJ, and the maximum peak power reaches 0.7 W.